The Effectiveness of Using Picture Series on Students’ English Writing Skills of Procedure Texts at SMA Masehi Sebiru Biru in Academic Year - Coki Andriano Tarigan; Azhary Tambusai (MUDABBIR Journal Reserch and Education Studies, 2023)
This research deals the effect of picture series on students in writing procedure text. The purpose of this study was to determine the effectiveness of the use of picture series on students' English procedural text writing skills. This research was conducted with experimental research used in two groups. the experimental group used media in the form of picture series and control without using picture series. The subjects of this study were students of SMA Masehi Sebiru Biru class XI MIA 1 who would be the experimental group and XI IIS which would be the control group, where class XI MIA 1 consisted of 29 students and XI IIS consisted of 24 students. This study used a written test to obtain data. After analyzing the data, the average value of the two groups was obtained where the experimental group got an average score of 85 and the control group 79.1. Based on the calculation results show that using the media in the form of picture series is higher than without using picture series. Picture series is effectively used in students writing procedure text.